2008
DOI: 10.1128/mcb.01759-07
|View full text |Cite
|
Sign up to set email alerts
|

Redundant Roles of Tead1 and Tead2 in Notochord Development and the Regulation of Cell Proliferation and Survival

Abstract: ؊/؊ mice appeared normal, but Tead1 ؊/؊ ; Tead2 ؊/؊ embryos died at embryonic day 9.5 (E9.5) with severe growth defects and morphological abnormalities. At E8.5, Tead1 ؊/؊ ; Tead2 ؊/؊ embryos were already small and lacked characteristic structures such as a closed neural tube, a notochord, and somites. Despite these overt abnormalities, differentiation and patterning of the neural plate and endoderm were relatively normal. In contrast, the paraxial mesoderm and lateral plate mesoderm were displaced laterally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(157 citation statements)
references
References 72 publications
(86 reference statements)
8
147
1
1
Order By: Relevance
“…The TEAD family of transcription factors, of which TEAD1 is the best characterised, regulate growth and differentiation in many tissues. This is exemplified by an important role for TEAD1 in embryonic development (Sawada et al, 2008;Zhang et al, 2008). TEAD1 binds several co-activators to stimulate the transcription of target genes (Gupta et al, 1997(Gupta et al, , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The TEAD family of transcription factors, of which TEAD1 is the best characterised, regulate growth and differentiation in many tissues. This is exemplified by an important role for TEAD1 in embryonic development (Sawada et al, 2008;Zhang et al, 2008). TEAD1 binds several co-activators to stimulate the transcription of target genes (Gupta et al, 1997(Gupta et al, , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Tead2-VP16 and Yap1 regulated largely overlapping sets of genes. However, only a few of the Tead/Yap1-regulated genes in NIH3T3 cells were affected in Tead1 Milewski et al, 2004;Nishioka et al, 2008;Sawada et al, 2008;Sawada et al, 2005;Yagi et al, 2007). Our recent study on Tead1;Tead2 double-mutant embryos revealed the genetic interactions between Tead1/2 and Yap1 during embryogenesis, and their necessity in cell proliferation and apoptosis .…”
Section: Mitsunori Ota and Hiroshi Sasaki*mentioning
confidence: 99%
“…TEAD factors clearly have redundant functions in vivo, as while TEAD2 knockout mice have only a minor phenotype, TEAD1/TEAD2 double-knockout mice have pleiotropic abnormalities that are much more severe than the loss of TEAD1 or TEAD2 alone. 8,34 Cell-specific regulation of proliferation genes by TEAD factors. In non-muscle cells, TEAD factors promote proliferation via Ctgf or Ccnd1.…”
Section: Tead4 Regulates Myoblast Differentiationmentioning
confidence: 99%